Management of Complications of Pancreatic Anastomoses - Schmid, Axel; Uder, Michael; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2017)
Background The pancreatic anastomosis may be the Achilles heel in pancreatic surgery. When a postoperative pancreatic fistula develops, be it mild or severe, in some cases life-threatening, POPF-associated complications can occur. Objectives Possibilities for the prophylaxis, diagnosis and therapy of POPF and POPF-associated complications in an interdisciplinary setting. Results Differentiated diagnostic and therapeutic management of POPF grade A - C is supported by recent studies to reduce morbidity and mortality. Depending on time and severity of POPF and POPF-associated complications, a conservative/interventional or surgical approach is indicated. Conclusion With the precise classification of POPF and POPF-associated complications, interdisciplinary diagnostic and therapeutic management can reduce morbidity and mortality after pancreatic surgery.
EVALuna2:15303